(untitled) (Journal of Rangpur Medical College, 2025)
Behcet’s disease is a vasculitis affecting small arteries and venules, more common in ’Silk Route’ countries, the Mediterranean, and Japan due to a strong genetic association with HLA-B51. Oral ulcers are common, with genital ulcers occurring in 60%-80% of cases. Skin lesions include erythema nodosum or acneiform, while migratory thrombophlebitis and vasculitis also occur. Ocular involvement is common, and neurological involvement occurs in 5%, mainly involving the brainstem with rare renal involvement. A 32-year-old lady presented with recurrent painful, herpetiform oral ulceration and painful genital ulceration, central retinal artery occlusion (CRAO) of left eye and intermediate uveitis of right eye with positive HLA-B51. J Rang Med Col. March 2025; Vol.10, No.1: 99-102